Enhancing Political Literacy Among Generation-Z Through Social Media: Evidence from Indonesia's Electoral Commission Instagram Account - Borneta, Farissa Avikass; Kurnia, Iervin Gilang; Setyowati, Ira; Sulfihidayatullah, Muh; Hayat, Muzahid Akbar (Potret Pemikiran, 2025)
The digitalization of political communication has significantly transformed how citizens engage with political information, particularly among younger generations. Generation Z (Gen Z), born between 1997 and 2012, represents a cohort of digital natives with high technological literacy but relatively limited political awareness. In Indonesia, where Gen Z constitutes a substantial share of the electorate, electoral institutions face challenges in delivering effective political education through conventional channels. This study examines the effectiveness of political education content disseminated via the @KPU_KALSEL Instagram account in enhancing political literacy among Gen Z students. Using a qualitative descriptive approach, the study conducted semi-structured interviews with five undergraduate students from the Faculty of Social and Political Sciences at UNISKA (born in 2002), supported by content analysis and systematic observation carried out in November 2024. The findings indicate that Instagram-based political content contributes positively to increasing political awareness and understanding among Gen Z audiences. Factors influencing effectiveness include content accessibility, visual clarity, concise messaging, and topical relevance. Posts related to the Peaceful Campaign Declaration and information on the Quiet Period were perceived as particularly impactful. Participants demonstrated improved comprehension of electoral procedures, regulations, and democratic values. This study concludes that social media platforms, when strategically utilized, can serve as effective tools for political education and voter engagement among digitally native generations.